Cluster — a new trend or necessity? - Markiewicz, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Enterprises from various industries are increasingly merging into cluster structures in which they see opportunities to develop their current activities and the opportunity to enter other markets. The theme of clusters is gaining increasing interest among business entities. This study analyses the phenomenon of clusters, based on the observations of several existing clusters. This essay focuses mainly on an analysis of the essence of clusters. Since the study is based on literature research, the article is theoretical in nature. The author assesses whether current cluster structures are just a temporary fashion, a new trend, or a real need of enterprises and concludes that clusters can provide economic benefits for regions and promote innovation
Keywords: cluster; cooperation; economy; innovation